PERLINDUNGAN HUKUM BAGI KONSUMEN ATAS KETIDAKSESUAIAN BARANG PESANAN PADA SITUS BELANJA ONLINE BLIBLI.COM - Heriyanto, (2023)
The development of information technology has added to people's habits in buying and selling transactions. Online transactions are a new way of conducting buying and selling activities utilizing advances in information technology. With the passage of time, the development of the online world using the internet has an impact that can be caused by new problems in the law, especially regarding consumer protection. There are several examples of losses experienced by consumers in online buying and selling transactions, namely: regarding goods that are not in accordance with the agreement between the business actor and the seller. In this study, the formulation of the problem to be discussed is how the legal protection for consumers for non-conformance of ordered goods in online shopping and the form of responsibility of business actors for non-conformance of ordered goods. The purpose of this study is to determine the legal protection for consumers for non-conformance of ordered goods in online shopping and to find out the form of responsibility of business actors for non-conformance of ordered goods. This study uses a normative juridical method which will refer to the legislation, containing Law Number 8 of 1999 concerning Consumer Protection and Law Number 11 of 2008 concerning Information and Electronic Transactions. Legal protection for consumers if the goods received by consumers are not in accordance with the order in the form of compensation. With the high interest in online shopping, it must be monitored properly so that consumers get the right legal protection and are not easily fooled or deceived by producers who are irresponsible and suffer losses in every buying and selling transaction, and pay attention to the applicable provisions in order to claim compensation. . Keywords: Legal protection, Consumers, Online Shopping